2008
DOI: 10.1371/journal.pone.0003971
|View full text |Cite
|
Sign up to set email alerts
|

UP States Protect Ongoing Cortical Activity from Thalamic Inputs

Abstract: Cortical neurons in vitro and in vivo fluctuate spontaneously between two stable membrane potentials: a depolarized UP state and a hyperpolarized DOWN state. UP states temporally correspond with multineuronal firing sequences which may be important for information processing. To examine how thalamic inputs interact with ongoing cortical UP state activity, we used calcium imaging and targeted whole-cell recordings of activated neurons in thalamocortical slices of mouse somatosensory cortex. Whereas thalamic sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
44
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 27 publications
(64 reference statements)
8
44
1
1
Order By: Relevance
“…In fact, models of auditory cortex neurons that incorporate representations of these excitability states have been shown to generate more short-ISI events, resulting in bimodal ISI distributions highly similar to those observed in our data (Britvina and Eggermont 2007). As cortical neurons tend to be desensitized to thalamic inputs during up states (Watson et al 2008), it is possible that during up states, neurons are only able to fire quick pairs of spikes when there is a preponderance of coincident thalamic inputs, corresponding to great certainty in the presence of a stimulus. This would explain the heightened feature selectivity we observed for short-ISI events.…”
Section: Discussionsupporting
confidence: 75%
“…In fact, models of auditory cortex neurons that incorporate representations of these excitability states have been shown to generate more short-ISI events, resulting in bimodal ISI distributions highly similar to those observed in our data (Britvina and Eggermont 2007). As cortical neurons tend to be desensitized to thalamic inputs during up states (Watson et al 2008), it is possible that during up states, neurons are only able to fire quick pairs of spikes when there is a preponderance of coincident thalamic inputs, corresponding to great certainty in the presence of a stimulus. This would explain the heightened feature selectivity we observed for short-ISI events.…”
Section: Discussionsupporting
confidence: 75%
“…During up states, neurons are more responsive and less selective, generating the overwhelming majority of spikes; changes between down and up states modulate feature tuning, because the precise nature of the stimulus features encoded in spiking is state dependent (Hasenstaub et al, 2007). Our results appear to differ from in vitro evidence that cortical activity is insensitive to thalamic input during up states (Watson et al, 2008); this may be because of differences between slice and in vivo conditions. Finally, we note that the present form of up-down oscillations is not found in awake behaving animals; instead, up states could be "fragments of wakefulness," corresponding to activated sensory awareness (Destexhe et al, 2007).…”
Section: Effect Of Up and Down Statescontrasting
confidence: 79%
“…The ␦ frequency band and the ISFs have been combined and referred to as slow cortical potentials or SCPs (Rockstroh et al, 1989). Because it is likely that this envelope of frequencies is not functionally homogeneous (Steriade et al, 1993;Petersen et al, 2003;Watson et al, 2008) it is important to understand exactly what is reported. As these references indicate, an important additional phenomenon falls into this frequency range, namely "up and down states," which have important effects on neuronal function and behavior through rhythmic changes in cell excitability.…”
Section: The Neurophysiology Of Boldmentioning
confidence: 99%